Evaluation of the Association between Obesity, Dietary Phytochemical Index, and Breast Cancer Risk and Knowledge Level - Çalışkan, Gözde; Güneşliol, B.E.; Akçadağ, N.S.; Tek, N.A. (Mattioli 1885, 2022)
Breast cancer is one of the most common cancers globally and has been reported as the leading cause of cancer-related death in women. Obesity is defined as one of the most important risk factors for breast cancer. Besides, oncological studies have reported that regular daily consumption of phytochemicals can reduce the risk of breast cancer. Therefore, this study aimed to clarify the association between obesity, dietary phytochemical index (DPI), breast cancer risk (BCR) and knowledge level (BCKL). Methods: This study was conducted with women aged 18 years and older. Participants filled out sociodemographic and lifestyle characteristics, anthropometric data, 24-hour retrospective food consumption records, BCR, and BCKL scales via Google forms. Body weight, height, and waist circumference (WC) were declared by the participants. BMI, waist to height ratio (WtHr), DPI, BCR and BCKL calculations were made by the researchers. Results: In terms of BCR, 94.2% of the participants were in the low, 3.3% in the medium, 0.3% in the high, and 2.2% in the highest risk group. Besides, there were significant differences between body weight, height, BMI, WC, and WtHr values of BCR groups. Yet, no significant difference was observed between the DPI of BCR groups. Moreover, DPI was not associated with BMI, WC, BCR, and BCKL. However, BMI was significantly correlated (moderate-to-strong) with WC and BCR (r=0.719 and r=0.605, respectively). Also, WC was significantly correlated (moderate) with BCR (r=0.475). The association between WC and BCKL (r=0.088) was statistically significant but not clinically. Conclusion: In conclusion, although BCR was not associated with DPI, it was associated with BMI and WC values, which are the indicators of obesity. In the light of this information, the associations between obesity, DPI, BCR, and BCKL will be understood more clearly in future studies with a large sample in which BCR groups have an equal distribution. © Mattioli 1885.
Keywords: breast cancer; Dietary phytochemical index; obesity; adult; aged; anthropometry; Article; body height; body mass; body weight; breast cancer; cancer risk; clinical evaluation; correlation coefficient; cross-sectional study; Dietary Phytochemical Index; disease association; female; food intake; high risk population; human; intermediate risk population; knowledge; lifestyle; lifestyle and related phenomena; low risk population; major clinical study; middle aged; normal value; nutritional assessment; obesity; retrospective study; risk factor; sociodemographics; waist circumference; waist to height ratio